2016
DOI: 10.1007/s11082-016-0823-4
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of a four-layer waveguiding nanocomposite structure in near-IR regime

Abstract: The theoretical study of the optical properties of TE-and TM-modes in a four-layer structure composed of the magneto-optical yttrium iron garnet guiding layer on a dielectric substrate covered by planar nanocomposite guiding multilayer is presented. The dispersion equation is obtained taking into account the bigyrotropic properties of yttrium-iron garnet, and an original algorithm for the guided modes identification is proposed. The dispersion spectra are analyzed and the energy flux distributions across the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…It is also shown that these structures can find their applications in the photonic devices controlled by the external fields [15], in designing the asymmetric and bidirectional nanophotonic devices which are used for the signal modulation/switching [16] and for the fabrication of highly efficient optical devices (optical switchers, filters, splitters, etc.) of the IR range [17].…”
Section: Introductionmentioning
confidence: 99%
“…It is also shown that these structures can find their applications in the photonic devices controlled by the external fields [15], in designing the asymmetric and bidirectional nanophotonic devices which are used for the signal modulation/switching [16] and for the fabrication of highly efficient optical devices (optical switchers, filters, splitters, etc.) of the IR range [17].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we propose a novel PBS based on grating mediated mode conversion. It is the grating, as a layer in a four-layer slab waveguide (FLSW) [17,18], that induces the mode conversion via the mechanism of grating diffraction to reflect back the TM-or TE-polarized light. Numerical simulation shows this compact PBS facilitates broadband, high polarization extinction ratio (PER) and large fabrication tolerance.…”
Section: Introductionmentioning
confidence: 99%